A histopathological and clinical assessment on the effect of microneedling on the autologous platelet-rich plasma in the experimental wound healing model - Ozkaya, Nese Kurt; Inan, Zeynep Deniz Sahin; Zereyak, Umut; Yilmaz, Sarper (Annals of Medical Research, 2021)
Aim: Platelet Rich Plasma (PRP) is a method used in dentistry and aesthetic applications in order to accelerate tissue healing. The purpose of this study is to assess the effect of PRP on accelerating wound healing and the contribution of microneedling application, i.e. multiple injection during PRP, and the volume effect of the PRP material to healing. Materials and Methods: In the study, 16 5-month-old male white New Zealand rabbits with an average weight of 2.7-3.0 kg were used. The four wounds were made on the back of each rabbit, and PRP, Normal saline(NS), microneedling(MN), and Sham procedures applied. Eight rabbits were sacrificed by taking their tissues for histological assessment at the end of 14 days. Epithelization, VEGF expression, angiogenesis, inflammatory cell, fibroblast, reticular fiber, and collagen parameters were evaluated. Eight rabbits were followed up for macroscopic healing. Result: The PRP procedure decreased the healing duration and wound area compared to other procedures(p<0.05). The NS procedure decreased the healing duration compared to the Sham procedure and provided a significant decrease in wound area compared to the MN and Sham procedures(p<0.05). Although the MN procedure decreased the wound area compared the Sham procedure, this difference was not statistically significant(p>0.05). PRP procedure increased staining scores and densities of epithelization, VEGF expression, angiogenesis compared to Sham procedure(p<0.05). PRP procedure increased staining score of collagen compared to Sham and NS procedures and staining density of collagen compared to other procedures(p<0.05). MN procedure decreased staining density of inflammatory cell compared to Sham procedure(p<0.05). Conclusion: The evaluation of simultaneous microneedling and PRP procedure on the 14th day of wound healing did not provide more positive synergistic effects on healing. In order to reduce the volume effect of the PRP amount given, the amount of PRP applied at each point should be as low as possible.